Predictive Value of Midline Spikes on Pediatric EEG for Seizure and Developmental Outcome. Issue 6 (November 2018) - Datta, Anita N.; Wallbank, Laura; Xu, Qi; Wong, Peter K. H.
Abstract : Purpose: Midline spikes are epileptiform discharges localized to the midsagittal regions of the brain. Isolated midline spikes are rare, but more common in children. Our objective was to determine whether midline spikes are predictive of seizure characteristics and neurodevelopment. Methods: EEGs and clinical information of 123 children with isolated midline spikes, and EEG follow-up within 12 to 24 months, were reviewed and compared with controls. Results: Most children with midline spikes had seizures (91%), with an equal predisposition to focal or generalized seizure semiology. There was no difference between the midline spike and control groups in terms of neonatal complications, seizure characteristics (type, frequency, and etiology), and neurologic examination findings. In patients with abnormal neuro-maging, deep gray or white matter abnormalities were more frequent in the midline group (41% vs. 13%, P = 0.02). The midline group had a higher risk of development delay (DD) than controls (43% vs. 29%, odds ratio: 1.8, 95% CI [1.1–3.2], P = 0.03). A higher risk of DD was also noted in the midline group in those aged less than 4 years (52% vs. 26%, odds ratio: 3.1, 95% CI [1.0–9.2], P = 0.04) and in those without seizures (40% vs. 17%, odds ratio: 3.16, 95% CI [1.1–8.8], P = 0.03). Conclusions: This is the largest reported group of patients with midline spikes. Midline spikes have a strong association with seizures and DD. Our data suggest that midline spikes result from heterogeneous etiologies, are more common in young children, and are not benign.